The Analysis of Work Accident Risk in Welding Process for Pipe Repair on Utility Boat PT LSM - Rachmianty, Andi; Pragawati, Ni Gusti Ayu Putu Dewi Armay; Ningrat, Andi; Usman, Arif Fudddin; Rusnaedi; Shauqy, Muhammad Azhar (Indonesian Journal of Maritime Technology, 2024)
PT LSM is a shipping company committed to focusing on providing integrated maritime services to support the oil & gas industry, PT LSM has a variety of offshore vessels to support these activities. LSM's shipping area is a rig area, where the area has a high level of danger and risk, therefore an adequate ship is needed both in crew and equipment on board. Especially in the piping system on board, if a leak occurs it can cause fatal things such as engine damage to an explosion and can cause work accidents such as fire and death. To minimize work accidents, risk hazard identification and risk control are made in each job, especially in piping work, namely pipe welding using the HIRADC method. This study used a descriptive qualitative method, in which the authors conducted field observations, interviews, and distributed questionnaires. The results of risk hazard identification, risk assessment and risk control will be entered in the HIRADC (Hazard Identification, Risk Assessment, and Determining Control) table. The conclusion of this study is that 43 hazards and 47 risks have been identified in pipe welding work. In the initial control, the low risk level was 42 risks (89.36%), the medium risk level was 5 risks (10.63%), and the high-risk level was 0 risks (0%). After further control of the identified risks, the risk level of medium risk (10.63%) has changed to low risk, so that all risk levels of the LSM Provider's ship pipe welding work have changed to a low risk level with a total of 47 risks (100%)). The controls used in pipe welding work are substitution, administration, and personal protective equipment (PPE).